PERANAN KEPALA DISTRIK DALAM IMPLEMENTASI KEBIJAKAN OTONOMI DAERAH DI DISTRIKAYAMARU UTARA KABUPATEN MAYBRAT PROPINSI PAPUA BARAT - Saba, Reni Liba; Rumapea, Patar; Ogotan, Martha (Sam Ratulangi University, 2016)
ABSTRACT : Situation of subdistrick head, and Implementation distraction of autonomy territorydifferent with another unit territory,because besides to take care of govermant publicassignment,subdistirc head also have assignment to handle autonomy territory affair to service societythat abundance by regent, Because subdistrict hend hold in importtantPart inside implementation autonomy territory at subdistrict.purpose of researth is find aut howimplementation autonomy territory at district Ayamaru Utara.Research method that use is qualitative.Method informant in this research as many astenperson whith taken from district government (for person)department upt/agensing territory (twoperson),head village (two person) BPD hend and LPM ( two person). Data accumulation that use byresearcher is interview technique.This qualitative analysis technique and interactive analysis methodtook from Miles and hubermen.Research contlusion result, base on ( 1 ) distict head to manage (activate,motivation,to build upand control) a potencial apparntur resourth and implantation an autonomy territory framework atdistrict Ayamaru Utara. ( 2 ) district head inside coordinatinggoverment work unit territory at regionwork district (UPT ) inside implementation framework of autonomy territory that already done whitgood enough however not give optimal result yet.Contlusion result base on researth so (1 ) district head of Ayamaru Utara inside to mÃ©nagepotential human resourch. Condition resourch whit subdistrict government of Ayamaru Utara whichgeneral still less/not enough so district head must be able and have a role inside to mÃ©nage potentialhuman resoutch apparatur. ( 2 ) district head inside Coordinating government unit work at workterritory of district Ayamaru Utara also be able to effective in coordinating meeting and consultancymeeting at district level..Key words: : District head part of implementation autonomy territory